Islamic Law: Between Revelation and Human Thoughts - Arifin, Zarul; Aji Haqqi, Abdurrahman Raden (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The revelation of religion teaches two ways to acquire knowledge. First, through revelation, which involves communication from God to humans; and second, through reason, which involves using impressions obtained by the five senses as food for thought to arrive at conclusions. Knowledge obtained through revelation is believed to be absolute, while knowledge obtained through reason is considered relative, requiring continuous testing and subject to being either true or false. In the pursuit of truth and enlightenment, a question arises in the age of scientific and technological advances: which form of knowledge is more trusted knowledge obtained through thought, knowledge obtained through revelation, or knowledge obtained through both? The focus of this research is to examine how revelation and human thought work together in establishing Islamic law. For example, when issuing contemporary fatwas for which there is no explicit argument from the Qur’an or Hadith, the ulama’ use reason or their intellects in formulating fatwas, ensuring that these fatwas do not conflict with the Qur’an or Hadith. The research method involves a literature review or literature study that includes theories relevant to the research problem. The goal of this research is to determine the relationship between Islamic law and human thought.